“MULHER PRESA PRA MIM É HOMEM”: DITADURA MILITAR E VIOLÊNCIA DE GÊNERO INSTITUCIONAL NA UNIVERSIDADE FEDERAL DO ESPÍRITO SANTO (1971-1973) - Pelegrine, Ayala Rodrigues Oliveira (2021)
This research aims to investigate the institutional gender violence practiced by the Brazilian State during the military dictatorship (1964-1985) against political activists at the Federal University of Espírito Santo (UFES). The time frame focuses on the years 1971 to 1973, the height of the regime's repressive action in social spaces seen as subversive. In this offensive, public universities represented privileged targets, once perceived as niches of communist ideas and values and practices contrary to morality. As agents of the State, the military – mostly men – went beyond the limits of their legitimate powers and committed countless violations against the human rights of university men and women. The latter, in military eyes, were worthy of the weight of such violations because they symbolized a double subversion: violators of the political order and of the moral order, of gender and sexuality. To understand military violence, this research seeks elements in the historical path of patriarchy in Brazil and uses the category institutional gender violence, understanding that the practice of torture by the military State was anchored in the manipulation of patriarchal definitions of femininity and masculinity. As a theoretical foundation, the dialogue between Cultural History and New Political History helps to understand how the patriarchal gender representations, shared by the military, produced an imagery that gave meaning to actions, behaviors, discourses and political devices that intended to control bodies, behaviors and women's social roles. Finally, in the recent scenario in favor of the truth of the military period in Brazil and the emergence of new sources for historical research, the methodological foundation of this research comes from the guidelines of the History of the Present Time for the treatment of documentary sources based on direct testimony and in the memory. The sources under analysis will be: the Report of the Truth Commission of the Federal University of Espírito Santo (CVUFES); the work In name of parents, by Matheus Leitão; the work Women and militancy: encounters and confrontations during the military dictatorship, by Ingrid Faria Gianordoli Nascimento, Zeidi Araújo Trindade and Maria de Fatima de Souza Santos; and the interview given by Laura Maria da Silva Coutinho to historian Mirela Marin Morgante. The testimonies of the following former students and activists of UFES in the period in question will be analyzed: Elizabete Santos Madeira, Laura Maria da Silva Coutinho, Maria Madalena Frechiani and Mirian Azevedo de Almeida Leitão.